Perirenalfat thickness is associated with bone turnover markers and bone mineral density in postmenopausal women with type 2 diabetes mellitus - Wang, Wei; Huang, Rong; Tang, Ping Tai; Tu, Mei; Guo, Xiu Li (Frontiers in Endocrinology, 2022)
Objectives Emerging evidence demonstrated that perirenal fat may modulate bone metabolism through several pathological pathways. This study was aimed to assess the associations between perirenal fat thickness (PrFT) and bone turnover markers (BTMs) and bone mineral density (BMD) in postmenopausal women with type 2 diabetes mellitus (T2DM) and further explore the correlation between PrFT and osteoporosis. Methods In this cross-sectional study, a total of 626 participants with complete data were enrolled in this study. Demographic and anthropometric information was collected. Biochemical parameters and BTMs were determined. PrFT and BMD were measured by computed tomography and dual-energy x-ray absorptiometry, respectively. Correlation analysis and regression models were used to assess the associations between PrFT and BTMs and BMD. The multiple binomial logistic regression model was used to estimate the independent variables of PrFT for osteoporosis. Results Overall, the prevalence of osteoporosis was 38.7%. PrFT was negatively correlated with β-cross-linked C-telopeptide of type I collagen (β-CTX) (r = -0.216,< 0.001), L1–L4 BMD (r = -0.351, < 0.001), and T-score (r = -0.396, < 0.001). PrFT also remained significantly correlated with β-CTX (β = -0.291, P< 0.001), L1–L4 BMD (β = -0.109, P= 0.027), and L1–L4 T-score (β = -0.149, P= 0.001) after adjustment for other confounding factors. Furthermore, PrFT was also independently associated with osteoporosis after adjustment for other confounding factors; the OR (95% CI) was 1.13 (1.04–1.23). PrFT also seems to have a relatively good identifying value for osteoporosis. The area under the curve (AUC) value of PrFT in identifying osteoporosis was 0.766 (95% CI: 0.705–0.826, P < 0.001). The optimal cutoff value of PrFT was 15.2 mm (sensitivity: 72.5%, specificity: 79.8%). Conclusions PrFT was significantly associated with β-CTX, BMD, and osteoporosis. These findings indicate that perirenal fat may play an important role in bone metabolism. Clinical Trial Registration http://www.chictr.org.cn/, identifier (ChiCTR2100052032).